Studies on genetic diversity and micropropagation of elite clones of Jatropha curcas L. - Kumar, Rajneesh (My University, 2020)
Massive anthropological activities such as rapid urbanization, industrialization, huge transportation lead to depletion of conventional and non-renewable fossil fuels on our planet and also significantly compromise the environmental health through the emission of greenhouse gases (GHG). This explains why eco-friendly biofuels namely bio-diesel and bio-ethanol have become focus areas of active research during the last few decades. Some of the important perennial non-edible tree borne oilseeds (TBOs) in the Indian subcontinent include Neem (A. indica A. Juss), Karanj (P. pinnata L. Pierre), Mahua (M. indica J.F. Gmel), Jatropha (Jatropha curcas L.) which produce seed oils suitable for biodiesel production. Jatropha curcas L. or physic nut, a member of the Euphorbiaceae family, is a multipurpose deciduous small tree or shrub is now distributed in many tropical and subtropical regions of Africa and Asia. J. curcas draws the attention of many researchers for their rapid growth, easy propagation, drought tolerance, pest resistance, and, most importantly, high seed yield and oil content, which are prerequisites for the quality biodiesel production. A thorough survey led to select a total of 31 morphologically superior candidate plus trees (CPTs) of J. curcas from different locations of Punjab, a North-Western state of India. The seed samples showed considerable variation with regard to shape, size and color of the seed coats. 100-seed weight ranged from 35.1077.34 g. Seed oil content was found to vary from 13.74% to 54.37%. Most of the accessions showed 3040% oil content, and a few accessions showed more than 40% oil content. J. curcas accessions having more than 30% seed oil content and seed yield approximately 1-2 kg/tree could be referred to as elite accessions consistent with operational guidelines of DBT, Govt. of India. Both genotypic and phenotypic variances were highest and comparable for 100-seed weight followed by seed oil content. Genotypic coefficient of variation and phenotypic coefficient of variation also showed similar pattern. The highest heritability of 99% was recorded for 100-seed weight followed by oil content (97%) and seed length (81%). Positive and significant correlation was observed between 100-seed weight and oil content (r = 0.517). The J. curcas accessions were distinctly grouped into 6 clusters on the basis of non-hierarchical K-Means cluster analysis. Out of 31 candidate plus trees (CPTs), 19 J. curcas accessions were studied for seed oil extraction, oil quality analysis and fatty acid composition. Most of the accessions showed more than 30% oil content with free fatty acid content ranging from 0.211.82%. The oil samples were transesterified efficiently to fatty acid methyl esters as evident from proton nuclear magnetic resonance (1H NMR) spectra. As revealed by gas chromatography, the contents of the four major fatty acids were found to significantly vary in the seed oils viz palmitic acid (8.6417.05%), stearic acid (4.347.94%), oleic acid (26.2646.36%) and linoleic acid (28.7253.78%). A number of seed oils showed high level of oleic acid (40.0246.36%), and some other oil samples were rich in linoleic acid (~45%). A simple and reproducible micropropagation protocol was adopted for in vitro clonal propagation of elite J. curcas germplasm through axillary shoot bud proliferation from nodal segments. MS medium supplemented with 2.0 mg/L BAP was found to be most effective in terms of percentage explant response (95.56 ± 3.72%), number of shoot buds (1.84 ± 0.06) and shoot length (1.32 ± 0.05 cm) per explant. MS media supplemented with 0.252.0 mg/L of TDZ resulted in swelling at cut ends of nodal and shoot tip explants with the only formation of a bunch of condensed adventitious shoot buds; no elongation was noticed by further sub-culturing on a medium supplemented with BAP alone or in combination with IBA. Multiplication of J. curcas shoot buds (8.66 ± 0.21 shoots of 2.21 ± 0.04 cm length per nodal segment) was carried out by repeated transfer and sub-culture of the nodal segments produced in vitro on MS medium supplemented with BAP 0.5 mg/L and IBA 0.25 mg/L. For rooting purpose, ½ strength MS supplemented with 3.0 mg /L IBA effectively worked in this study. In this media formulation, 75.12 ± 4.33% shoots responded and produced 3.38 ± 0.09 roots of 4.29 ± 0.09 cm length. The in vitro raised rooted J. curcas plantlets were acclimatized by slow and gradual exposure from high RH and low-temperature conditions to low RH and high-temperature conditions. The elite J. curcas accessions as characterized in this study, will be useful in terms of germplasm exchange, mass propagation, multilocation trials, biodiesel feedstocks, other industrial uses, and importantly as prebreeding materials for genetic improvement of this bioenergy crop. Moreover, development of a simple, efficient and true-to-type in vitro clonal propagation protocol is promising to produce the quality planting materials for field trials and large scale cultivation.
Keywords: Jatropha curcas L.; Seed traits; Oil content; Genetic and phenotypic variation; Fatty acid composition; Micropropagation